Case Report: Bladder endometriosis presenting as a bladder mass – diagnosis and surgical management - Chen, Junhao; Li, Zhaojiao; Chen, Bo; Zhao, Junxian; Zuo, Jieming; Wang, Haifeng; Fu, Shi (Frontiers in Medicine, 2025)
Endometriosis (EMs) is a common disease in women of childbearing age, categorized into ovarian, superficial, and deep infiltrating endometriosis (DIE). Bladder endometriosis (BE) is a type of DIE with an incidence of approximately 1% among women of childbearing age. Its main symptoms include pelvic discomfort and urinary dysfunction. Importantly, bladder endometriosis and ureteral endometriosis are distinct entities with different clinical manifestations and management approaches. As the condition progresses, it can involve the ureters, leading to hydronephrosis and severe renal function impairment. Currently, diagnosis primarily relies on ultrasound, MRI, and cystoscopy, with surgical treatment showing good efficacy and low recurrence rates. We report a patient with bladder endometriosis to enhance our understanding of this condition.